Responsabilidad social y turismo inclusivo en la Matriz del Cantón Penipe, Provincia de Chimborazo - Vera Luzuriaga, Jorge Alejandro (2019)
This study is focusing on the analysis of the contribution of social responsibility to inclusive tourism. In the matrix of Canton Penipe, Province of Chimborazo as tourist destinations face daily changes on the current tourism environment with new growing alternatives for the competitiveness of opportunities, behavior, and enjoyment of the tourist, especially the demand for facilities and services that a person with physical disabilities requires. Therefore, this research looks into unique and accessible tourism of people with physical disabilities and who currently integrate a large number of inhabitants in the market. It is also a growing and potential element for future tourism businesses that contribute to the local economy and satisfaction of the tourist. This investigation is descriptive and explanatory, which presented a transversal non-experimental design of the descriptive type with the application of this design, searching the influence between the variables. The research uses different techniques and instruments such as: Direct observation, survey for the data collection on general information, social improvement, economic contribution, environmental respect, tourism inclusion, equal opportunities, and tourism activity. The data are obtaining through the surveys, the help to understand the current situation of social responsibility, and inclusive tourism. The hypothesis' test was carried out; it allowed us to deduce that social responsibility significantly influences inclusive tourism. Finally, conclusions, recommendations, and a proposal for an inclusive manual as an alternative for social development for the city of Penipe are making.